Granulocyte‐macrophage colony‐stimulating factor reverses Alzheimer's disease pathology in the tgf344‐AD rat model. (1st February 2022) - Ahmed, Md. Mahiuddin; Wang, Athena Ching‐Jung; Boyd, Timothy D.; Solano, D. Adriana; Vielle, Anne; Markham, Neil; Coughlan, Christina M; Chial, Heidi J; Vergara, M. Natalia; Potter, Huntington
Abstract: Background: Granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), a hematopoietic growth factor, has shown therapeutic and neuroprotective effects in animal models of Alzheimer's disease (AD), Parkinson's disease, Down syndrome, and stroke. In a retrospective study, we reported that recombinant human GM‐CSF (sargramostim) treatment led to improved cognition in patients with cognitive impairment due to chemotherapy. Our recently completed Phase 2 clinical trial in AD showed that sargramostim treatment increased toward normal both MMSE scores and plasma biomarkers of neurodegeneration. Cohen et al. (2013) developed a transgenic rat model (TgF344‐AD) that expresses the Swedish mutant human APP (APPsw) and mutant human presenilin 1 (PSEN1) genes that cause familial AD. Interestingly, in addition to cerebral amyloidosis, neuronal loss, and cognitive deficits, TgF344‐AD rats also show age‐dependent tauopathy including overexpression of phosphorylated tau and neurofibrillary tangle formation, which do not arise in mouse models of AD. To evaluate the potential ability of GM‐CSF to reverse and/or prevent the full range of AD pathology, we treated ∼20‐month‐old TgF344‐AD rats with GM‐CSF or saline, and investigated AD pathology in the brain and retina. We also analyzed biomarkers in plasma using Meso Scale Discovery (MSD) and SIMOA neuroinflammation panels. Method: TgF344‐AD rats were injected subcutaneously with GM‐CSF (83.3 ug/kg/day; 5 days/week) or with saline (200 ul/day) for 24 injections total over 32 days. On day 32, blood samples were collected, plasma samples were isolated, and brain and retina tissues were processed for immunohistochemistry and immunoblotting. Result: TgF344‐AD rats treated with GM‐CSF showed a significant reduction in amyloid plaque deposition in the cortex compared to saline‐treated TgF344‐AD rats. We also observed a trend of reduced amyloid plaques in the CA region of the hippocampus (p=0.06) in GM‐CSF‐treated TgF344‐AD rats. In ongoing experiments, we are investigating the effects of GM‐CSF treatment on tauopathy and neuroinflammation in the brain and retina and on plasma biomarkers. Conclusion: Although experiments are in progress, our preliminary findings indicate that GM‐CSF treatment rescues some AD pathology in TgF344‐AD rats. Complete results will determine the therapeutic potential for GM‐CSF/sargramostim/Leukine® not only for reducing amyloidosis, but also on other relevant pathological manifestations of AD.